Demokrasi di Layar Wayang: Cara Baru Mentransformasi Ajaran Kepemimpinan Hindu - I Wayan Winaja (Pusat Kajian Bali Universitas Udayana, 2016)
Wayang is the traditional performing arts whose the story contains many moral teachings, ethics, and mrality. Shows (art of pakeliran) screen puppet, not only as spectacle but also as a guide. This article analyzes the transfomation of the Hindu leadership values throught at pakeliran. The purpose of the study is to increase the appreciation of literature, namely preserving and developing traditional works especially oral literature play shadow puppets Bali especially about Hinduism leadership values. Methods of analysis using cultural study approach with descriptive analytic method. The theory used to analyze is the deconstruction theory, and the theory of Critical Education. Conclusions from this research is the transfomation of value not only carried out on formal education (schooling) but also through education can no scholling through art of pakeliran.